Emotional intelligence, self-efficacy, english language proficiency and cross cultural adjustment among China self-initiated expatriates in Malaysia - Ma, Chengyan (2014)
Cross-cultural adjustment (CCA) is a vital part of expatriate accomplishments, it is a kind of adjustment that can be improved by exposing the expatriates to the facts and understanding of norms that is suitable for behaviors that are exhibited in a foreign country by means of cross-cultural adjustment. This research aims to ease interactions between China Self-Initiated Expatriates (SIEs) and national hosts via Emotional Intelligence, Self-efficacy and English language proficiency, thus offering expatriates a vision into the host country’s culture to enhance their understanding of the new environment. Social Cognitive theory suggest that individuals form and display certain behavioral patterns which are categorized into three; personal factors, behavioral factor, and environmental. This current research uses the sample size of 87 SIEs respondents from China mainland which are selected via systematic random sampling. The questionnaire used in this research was a combination of constructed questions and adapted questions from previous studies. The three variables which are Emotional Intelligence, Self-efficacy and English language proficiency, and CCA was analyzed with Pearson correlation and multiple regressions with Statistical Package for Social Science (SPSS). The result was presented in a descriptive and inferential manner. It exhibited that China SIEs in Malaysia were able to adjust well in Malaysia due to good Emotional Intelligence, Self-Efficacy and proficiency in English language. The findings also suggests that Self-Efficacy and Emotional Intelligence contributed significantly to CCA by the China SIEs while English language proficiency was found not to contribute drastically to enhance China expatriates’ adjustment in Malaysia. It is recommended for future research to incorporate bigger sample size to further increase the accuracy of the research